2015
DOI: 10.3389/fpubh.2015.00182
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Multi-Scale Co-Occurrence Patterns of Asthma and Influenza with Oak Ridge Bio-Surveillance Toolkit

Abstract: We describe a data-driven unsupervised machine learning approach to extract geo-temporal co-occurrence patterns of asthma and the flu from large-scale electronic healthcare reimbursement claims (eHRC) datasets. Specifically, we examine the eHRC data from 2009 to 2010 pandemic H1N1 influenza season and analyze whether different geographic regions within the United States (US) showed an increase in co-occurrence patterns of the flu and asthma. Our analyses reveal that the temporal patterns extracted from the eHR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The results indicate that although normalization may speed up processing [21], it has an unpredictable effect on the estimation of the number of components k. We therefore recommend that, at least for the purpose of estimating k, data not be normalized. Indeed, this is the approach that has been taken in much of the public health and environmental science literature using NMF [5,6,8,9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results indicate that although normalization may speed up processing [21], it has an unpredictable effect on the estimation of the number of components k. We therefore recommend that, at least for the purpose of estimating k, data not be normalized. Indeed, this is the approach that has been taken in much of the public health and environmental science literature using NMF [5,6,8,9].…”
Section: Discussionmentioning
confidence: 99%
“…We therefore recommend that, at least for the purpose of estimating k , data not be normalized. Indeed, this is the approach that has been taken in much of the public health and environmental science literature using NMF [ 5 ], [ 6 ], [ 8 ], [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For younger patients, their age-dependent risk could be modeled, but this requires accurate determination of age of onset, which is problematic, and the older patients may be older than the EMR, so their diagnoses of early-onset diseases will be recorded at misleadingly later ages, if recorded at all. Unfortunately, co-occurrence of disease codes, without correction for age (or, if appropriate, gender), is often used to establish disease comorbidity [45, 46, 47, 48, 49, 50]. Wong et al [51] did use age and sex stratification to compute observed/expected ratios to examine multimorbidity.…”
Section: Comorbiditymentioning
confidence: 99%